Recent Advances in Carbon Nanotubes for Nervous Tissue Regeneration - Redondo, Carlos (2019)
Nanomedicine has allowed for emerging advances in imaging, diagnostics and therapeutics. Regenerative Medicine has taken advantage of a number of nanomaterials for reparation of diseased or damaged tissues in the nervous system involved in memory, cognition and movement. Electrical, thermal, mechanical and biocompatibility aspects of carbon-based nanomaterials (nanotubes, graphene, fullerenes and their derivatives) make them suitable candidates to drive nerve tissue repair and stimulation. This review article focuses on recent advances on the use of carbon nanotube (CNT)-based technologies on nerve tissue engineering; outlining how neurons interact with the nanomaterials interface for promoting neuronal differentiation, growth and network reconstruction for their possible use in therapies of neurodegenerative pathologies and spinal cord injuries.